Voice activated: a transformative approach to language learning. (4th March 2022) - Macdonald, Sheila; Watson, Jodi
ABSTRACT: This article explores a cross-disciplinary collaboration within English for Speakers of Other Languages (ESOL) provision for adults born outside the United Kingdom (UK). By foregrounding collaborative practice between a language practitioner and an artist, we offer a practical experience of working beyond and besides language which offers both an example and a challenge to academics seeking to analyse arts-informed educational practice. We propose that attention to voice in ESOL can make a significant contribution to achieving the complementary aims of confidence in the target language and developing multilingual, multi-directional community integration.